Community Work as Opposition: Tensions and Potentials in a Formalistic Welfare Context (Journal of Comparative Social Work, 2020)
A number of tensions pertaining to social problems and human suffering become apparent when analysing community work in a Danish welfare setting. As a source for critical reflection, we discern some of these challenges, but also potentials, which relate not only to a Danish context, but to challenges in any highly institutionalized welfare system. Three community work social enterprises serve to exemplify the objectives of addressing social problems by fostering participation and empowerment. To enhance and include the voice of service users, the programmes attempt to cultivate human resources as opposed to perceived formalism and a subsequent diminishment of the potentials of community inclusion. The formalistic governmental agendas are perceived to be unable to appreciate the diversity of service users’ individual needs and social challenges, which produces conflicting prospects. Such a dichotomy between formalistic welfare practices and the ideals represented in the three enterprises offers a podium for users, professionals, policymakers and researchers to consider alternative expressions of community work, and how these can address social problems. We maintain that rapidly changing welfare models require an increased sensitivity to human suffering as a position embedded in the habitus and sociological imagination of community work. It is a source for reflection on the role of welfare arenas perceived as spaces in which service users ideally, based on their own social situation, can improve their social circumstances. It is an invitation to reflect on the potentials of community work in a diversity of cultures and practices.